a.) We begin by describing how you define the square root of an
operator. If you have ever computed the square root of a matrix, then
this will be familiar.
Consider a nonnegative operator \(\hat{O}\) (nonnegative means that all
eigenvalues satisfy \(\lambda\ge 0\)).
In its eigenbasis, it is represented as a diagonal matrix, with
eigenvalues on the diagonal. \[\left\langle
m\middle|\hat{O}\middle|n\right\rangle=\begin{pmatrix}o_1 &0 &0
\\0 &\ddots&0 \\0 &0 & o_n\end{pmatrix}\] To make
the square root, we use the same eigenvectors but take the square root
of each eigenvalue \[\left\langle
m\middle|\sqrt{\hat{O}}\middle|n\right\rangle=\begin{pmatrix}\pm\sqrt{o_1}
&0& 0\\ 0&\ddots& 0 \\0 & 0&
\pm\sqrt{o_n}\end{pmatrix}\] Obviously, any pattern of \(+\) or \(-\) signs gives a valid square root
operator, such that \(\left(\sqrt{\hat{O}}\right)^2=\hat{O}\),
but, of course, we would like to define it uniquely if we can.
Show that there is only one choice of \(\sqrt{\hat{O}}\) that is also positive
semidefinite (nonnegative).
Explain further why any operator that commutes with \(\hat{O}\) must also commute with \(\sqrt{\hat{O}}\).
b.) Using the definition \(\hat{r}^2=\hat{r}_x^2+\hat{r}_y^2+\hat{r}_z^2\)
and \([\hat{r}_\alpha,\hat{p}_\beta]=i\hbar\delta_{\alpha\beta}\)
find \([\hat{p}_\alpha,\hat{r}^2]\).
c.) Use the Leibniz rule to show \[[\hat{p}_\alpha,\hat{r}]=-i\hbar\frac{\hat{r}_\alpha}{\hat{r}}\]
Note: you may assume \([\hat{p}_\alpha,\hat{r}]\) commutes with
\(\hat{r}\).
d.) Use the Jacobi identity to evaluate \([\hat{r}^2,[\hat{r},\hat{p}_\alpha]]\), but
you cannot assume that \([\hat{r},[\hat{r},\hat{p}_\alpha]]=0\)
anymore. Instead use the result from part (c) before you made that
assumption. You should be able to prove that \([\hat{r}^2,[\hat{r},\hat{p}_\alpha]]=0\).
But then, part (a) implies \([\hat{r},[\hat{r},\hat{p}_\alpha]]=0\), so
your calculation in part (c) is justified.
e.) Use Leibniz rule on \([\hat{p}_\alpha,\frac{\hat{r}}{\hat{r}}]\)
to find \([\hat{p}_\alpha,\frac{1}{\hat{r}}]\).
In spherical coordinates we have \[\begin{aligned}
\mathbf{e}_r=& \
(\sin{\theta}\cos{\phi},\sin{\theta}\sin{\phi},\cos{\theta}) \\
\mathbf{e}_\theta=& \
(\cos{\theta}\cos{\phi},\cos{\theta}\sin{\phi},-\sin{\theta}) \\
\mathbf{e}_\phi=& \ (-\sin{\phi},\cos{\phi},0)
\end{aligned}\] Using the quantum analog \(\hat{\mathbf{e}}_r=\frac{\hat{\mathbf{r}}}{\hat{r}}\),
we determined a Hermitian radial momentum \(\hat{p}_r=\frac{1}{2}(\hat{\mathbf{e}}_r\cdot\hat{\mathbf{p}}+\hat{\mathbf{p}}\cdot\hat{\mathbf{e}}_r)\)
in the lecture, and put it into canonical form with all coordinate
operators on the left. In doing so, we found a quantum correction.
a.) Carry out the same calculation for the \(\theta\) component of momentum to find
\[\hat{p}_\theta=\frac{1}{2}(\hat{\mathbf{e}}_\theta\cdot\hat{\mathbf{p}}+\hat{\mathbf{p}}\cdot\hat{\mathbf{e}_\theta})\]
and move all coordinate operators to the left. Express your final answer
in terms of \(\cos{\hat{\theta}},\sin{\hat{\theta}},\cos{\hat{\phi}},\sin{\hat{\phi}},\hat{r}\)
and \(\hat{p}_x,\hat{p}_y,\hat{p}_z\).
This case also has a quantum correction. Note that \(\cos{\hat{\theta}}=\frac{\hat{r}_z}{\hat{r}},\sin{\hat{\theta}}\cos{\hat{\phi}}=\frac{\hat{r}_x}{\hat{r}},\)
and \(\sin{\hat{\theta}}\sin{\hat{\phi}}=\frac{\hat{r}_y}{\hat{r}}\)
b.) Repeat for the \(\phi\) component
\[\hat{p}_\phi=\frac{1}{2}(\hat{\mathbf{e}}_\phi\cdot\hat{\mathbf{p}}+\hat{\mathbf{p}}\cdot\hat{\mathbf{e}_\phi}).\]
Note that this notation for \(\hat{p}_\theta\) and \(\hat{p}_\phi\) is not the same as what many
authors use (because they discuss the canonical momentum, not the
projection along the spherical unit vectors). For us, it is the
component of angular momentum along the corresponding unit vector
direction.
a.) The Laguerre polynomial is defined by \[L_k^{2l+1}(x)=\sum_{j=0}^k\begin{pmatrix}2l+k+1\\k-j\end{pmatrix}\frac{(-x)^j}{j!}\]
where \(\begin{pmatrix}m\\n\end{pmatrix}=\frac{m!}{n!(m-n)!}\)
is the binomial coefficient.
Writing the Laguerre polynomial as \[L_k^{2l+1}(x)=\sum_{j=0}^ka_j^{2l+1;k}x^j\]
compute the ratio \(\frac{a_{j+1}^{2l+1;k}}{a_j^{2l+1;k}}\) and
express your result in simplest terms as the ratio of one integer in the
numerator divided by the product of two integers in the
denominator.
b.) Under the assumption that the state \(\left|n,l=n-1\right\rangle\) is normalized,
show that the eigenstate of hydrogen can be written as \[\left|n,l\right\rangle=(-i)^{n-l-1}\left(\frac{na_0}{2\hat{r}}\right)^{n-l-1}\sqrt{\frac{(2n-1)!(n-l-1)!}{(n+1)!}}L_{n-l-1}^{2l+1}\left(\frac{2\hat{r}}{na_0}\right)\left|n,l=n-1\right\rangle\]
To do this, we must first verify that \[\begin{gathered}
\hat{B}_r^\dagger(l)\hat{B}_r^\dagger(l+1)\cdots\hat{B}_r^\dagger(n-2)\left|n,l=n-1\right\rangle=\left(\frac{-i\hbar}{\sqrt{2\mu}na_0}\right)^{n-l-1}\left(\frac{na_0}{2\hat{r}}\right)^{n-l-1}\frac{(2n-1)!}{(n+l)!}\frac{(n-l-1)!
\ l!}{(n-1)!} \\ \times
L_{n-l-1}^{2l+1}\left(\frac{2\hat{r}}{na_0}\right)\left|n,l=n-1\right\rangle
\end{gathered}\] We do this by computing the coefficient of the
\(\hat{r}^0\) term. Verify from the
string of radial raising operators that this coefficient is \[\left(\frac{i\hbar}{\sqrt{2m}na_0}\right)^{n-l-1}\frac{(2n-1)!
\ l!}{(n+l)!(n-1)!}\left|n,l=n-1\right\rangle\] Show you get the
same result from the Laguerre polynomial.
We solve for the eigenstates of hydrogen using the full Schrödinger
methodology. This has us start with the ground state for a given \(l\) and compute the excited states with
\(n>l+1\) using the procedure of
interchanging \(\hat{A}^\dagger\) and
\(\hat{A}\) and refactorizing.
We work in the angular momentum \(l\)
subspace, so our first Hamiltonian is \[\begin{aligned}
\hat{H}_0^{(l)}=\hat{H}_l=& \
\hat{B}_r^\dagger(l)\hat{B}_r(l)+\tilde{E}_l \\
=& \ \hat{A}_0^\dagger(l)\hat{A}_0(l)+E_0
\end{aligned}\] The ground state of \(\hat{H}_l\) satisfies \(\hat{B}(l)\left|n{=}l+1,l\right\rangle=0\)
and \(E_0=\tilde{E}_l\). Denote \(\left|\phi_0\right\rangle=\left|n{=}l+1,l\right\rangle\)
The first auxiliary Hamiltonian is \[\hat{H}_1^{(l)}=\hat{A}_0^{(l)}\hat{A}_0^{\dagger(l)}+E_0\]
Show that \[\begin{aligned}
\hat{H}_1^{(l)}=\hat{H}_{l+1}=& \
\hat{B}_r^\dagger(l+1)\hat{B}_r(l+1)+\tilde{E}_{l+1} \\
=& \ \hat{A}_1^\dagger\hat{A}_1+E_1.
\end{aligned}\] We form \(\left|\phi_1\right\rangle\) via \[\hat{A}_1\left|\phi_1\right\rangle=0\implies\hat{B}_r(l+1)\left|\phi_1\right\rangle=0\]
and \(\left|\psi_1\right\rangle\) via
\[\hat{A}_0^\dagger\left|\phi_1\right\rangle=\hat{B}_r^\dagger(l)\left|\phi_1\right\rangle=\hat{B}_r^\dagger(l)\left|n=l+2,l+1\right\rangle\]
Explain how this \(\left|\psi_2\right\rangle\) is correctly
the state \(\left|n{=}l+2,l\right\rangle\) and how
\(E_1=\tilde{E}_{l+1}\). Complete the
calculation to find all eigenstates and energies. Note this is
essentially a “bookkeeping” exercise as all the hard work has already
been done.
We derive \(\hat{\mathbf{p}}^2=\hat{p}_r^2+\frac{\hat{\mathbf{L}^2}}{\hat{r}^2}\)
in a different way.
a.) Assume that \(\hat{\mathbf{A}}\)
and \(\hat{\mathbf{B}}\) are both
vector operators. They need not commute. Then, \[\begin{aligned}
(\hat{\mathbf{A}}\times\hat{\mathbf{B}})^2=& \
\sum_{ijklm}\varepsilon_{ijk}\varepsilon_{lmk}\hat{A}_i\hat{B}_j\hat{A}_l\hat{B}_m
\\
=&
\sum_{ijlm}(\delta_{il}\delta_{jm}-\delta_{im}\delta_{jl})\hat{A}_i\hat{B}_j\hat{A}_l\hat{B}_m
\\
=& \
\hat{\mathbf{A}}^2\hat{\mathbf{B}}^2+\sum_{ij}\hat{A}_i[\hat{B}_j,\hat{A}_i]\hat{B}_j
\\
-& \
(\hat{\mathbf{A}}\cdot\hat{\mathbf{B}})^2-\sum_{ij}\left(\hat{A}_i\hat{B}_j[\hat{A}_j,\hat{B}_i]-\hat{A}_i\hat{B}_i[\hat{A}_j,\hat{B}_j]\right)
\end{aligned}\] assuming \([\hat{A}_i,\hat{A}_j]=[\hat{B}_i,\hat{B}_j]=0\).
b.) Pick \(\hat{\mathbf{A}}=\hat{\mathbf{r}}\) and
\(\hat{\mathbf{B}}=\hat{\mathbf{p}}\)
to show \[(\hat{\mathbf{r}}\times\hat{\mathbf{p}})^2=\hat{\mathbf{r}}^2\hat{\mathbf{p}}^2-(\hat{\mathbf{r}}\cdot\hat{\mathbf{p}})^2+i\hbar
\ \hat{\mathbf{r}}\cdot\hat{\mathbf{p}}\] Use this to then verify
that \[\hat{\mathbf{p}}^2=\hat{p}_r^2+\frac{\hat{\mathbf{L}}^2}{\hat{r}^2}.\]
Hint: You need \[\frac{1}{\hat{r}^2}(\hat{\mathbf{r}}\cdot\hat{\mathbf{p}})^2=\frac{1}{\hat{r}}(\hat{\mathbf{r}}\cdot\hat{\mathbf{p}})\frac{1}{\hat{r}}(\hat{\mathbf{r}}\cdot\hat{\mathbf{p}})+\text{quantum
correction}.\]